Non-destructive evaluation of delamination defects in carbon fibre composites by X-ray diffraction - Leong, Hannah Yoke Fun. (2009)
With the increased use of composites in aircraft structures, the demand for effective methods of maintenance for safety and quality purposes would increase correspondingly. The X-ray diffraction method is a relatively established non-destructive inspection technique applicable to composite materials. This project establishes a technique based on X-ray diffraction for non-destructive detection and characterisation of delamination defects in carbon fibre composite laminated structures. 3D Computed Tomography is used as a supplementary technique to support the evaluation of these defects. Samples are manufactured both with and without artificial delaminations embedded and their X-ray diffraction profiles compared. Two key relationships are employed to correlate the results from the X-ray diffraction profiles to the yield strength of the material: the Scherrer equation to determine crystallite size, and the Hall-Petch relationship to relate the crystallite size to yield strength. It is observed that the average crystallite size of the samples with delamination defects is 20-25% larger than that of the intact samples. As a result, these samples are predicted to have lower yield strengths. This is consistent with grain-boundary strengthening theory: the artificial delamination severely disrupts the crystalline structure in the carbon fibre, thus dislocations are able to be displaced more easily through the material, leading to a drop in yield strength. 3D Computed Tomography imaging visualises the presence of air gaps between the artificial delamination and surrounding material, supporting the validity of the results for real delamination defects where debonding occurs.